MACROINVERTEBRATES OF PEDID RIVER AND THE TRIBUTARIES - Jongkar, Grinang; Anita, Muli; Muhammad Ashiq Muzakkir, Ahmad Thani; Gabriel Tonga, Noweg; Cindy, Peter (UNIMAS Publisher, 2023)
The stream’s drainage of Bungo Range constitutes first to third orders, fast flowing water and rocky substrates. The water of the streams is tea-coloured in appearance during dry period due to tannin contain which is associated with kerangas forest in the catchment. Sg Pedid is the main drainage system in the upstream feed by numerous second and first orders before discharge to Sarawak Kanan River – main basin in Kuching Division.